Promoting Shared Decision-Making Behaviors During Inpatient Rounds: A Multimodal Educational Intervention. (July 2019) - Harman, Stephanie M.; Blankenburg, Rebecca; Satterfield, Jason M.; Monash, Brad; Rennke, Stephanie; Yuan, Patrick; Sakai, Debbie S.; Huynh, Eric; Chua, Ian; Hilton, Joan F.
Abstract : Purpose: To estimate the effectiveness of a multimodal educational intervention to increase use of shared decision-making (SDM) behaviors by inpatient pediatric and internal medicine hospitalists and trainees at teaching hospitals at Stanford University and the University of California, San Francisco. Method: The 8-week Patient Engagement Project Study intervention, delivered at four services between November 2014 and January 2015, included workshops, campaign messaging, report cards, and coaching. For 12-week pre- and postintervention periods, clinician peers used the nine-point Rochester Participatory Decision-Making Scale (RPAD) to evaluate rounding teams' SDM behaviors with patients during ward rounds. Eligible teams included a hospitalist and at least one trainee (resident, intern, medical student), in addition to nonphysicians. Random-effects models were used to estimate intervention effects based on RPAD scores that sum points on nine SDM behaviors per patient encounter. Results: In total, 527 patient encounters were scored during 175 rounds led by 49 hospitalists. Patient and team characteristics were similar across pre- and postintervention periods. Improvement was observed on all nine SDM behaviors. Adjusted for the hierarchical study design and covariates, the mean RPAD score improvement was 1.68 points (95% CI, 1.33–2.03; P < .001; Cohen d = 0.82), with intervention effects ranging from 0.7 to 2.5 points per service. Improvements were associated with longer patient encounters and a higher percentage of trainees per team. Conclusions: The intervention increased behaviors supporting SDM during ward rounds on four independent services. The findings recommend use of clinician-focused interventions to promote SDM adoption in the inpatient setting. Abstract : Supplemental Digital Content is available in the text.